The reciprocal relationship between executive function and theory of mind in middle childhood: a 1-year longitudinal perspective - Austin, Gina; Groppe, Karoline; Elsner, Birgit (Frontiers in Psychology, 2014)
There is robust evidence showing a link between executive function (EF) and theory of mind (ToM) in 3- to 5-year-olds. However, it is unclear whether this relationship extends to middle childhood. In addition, there has been much discussion about the nature of this relationship. Whereas some authors claim that ToM is needed for EF, others argue that ToM requires EF. To date, however, studies examining the longitudinal relationship between distinct subcomponents of EF (i.e. attention shifting, WM updating, inhibition) and ToM in middle childhood are rare. The present study examined 1) the relationship between three EF subcomponents (attention shifting, WM updating, inhibition) and ToM in middle childhood, and 2) the longitudinal reciprocal relationships between the EF subcomponents and ToM across a one-year period. EF and ToM measures were assessed experimentally in a sample of 1,657 children (aged 6 to 11 years) at time point one (t1) and one year later at time point two (t2). Results showed that the concurrent relationships between all three EF subcomponents and ToM pertained in middle childhood at t1 and t2, respectively, even when age, gender, and fluid intelligence were partialled out. Moreover, cross-lagged structural equation modeling (again, controlling for age, gender, and fluid intelligence, as well as for the earlier levels of the target variables), revealed partial support for the view that early ToM predicts later EF, but stronger evidence for the assumption that early EF predicts later ToM. The latter was found for attention shifting and WM updating, but not for inhibition. This reveals the importance of studying the exact interplay of ToM and EF across childhood development, especially with regard to different EF subcomponents. Most likely, understanding others’ mental states at different levels of perspective-taking requires specific EF subcomponents, suggesting developmental change in the relations between EF and ToM across childhood.